Parasympathetic Neural Activity Accounts for the Lowering of Exercise Heart Rate at High Altitude - Boushel, R.; Calbet, J.-A.; Rådegran, G.; Sondergaard, H.; Wagner, P. D.; Saltin, B. (Circulation, 2001)
Background: In chronic hypoxia, both heart rate (HR) and cardiac output (Q) are reduced during exercise. The role of parasympathetic neural activity in lowering HR is unresolved, and its influence on Q and oxygen transport at high altitude has never been studied. Methods and Results: HR, Q, oxygen uptake, mean arterial pressure, and leg blood flow were determined at rest and during cycle exercise with and without vagal blockade with glycopyrrolate in 7 healthy lowlanders after 9 weeks` residence at 5260 m (ALT). At ALT, glycopyrrolate increased resting HR by 80 bpm (73±4 to 153±4 bpm) compared with 53 bpm (61±3 to 114±6 bpm) at sea level (SL). During exercise at ALT, glycopyrrolate increased HR by 40 bpm both at submaximal (127±4 to 170±3 bpm; 118 W) and maximal (141±6 to 180±2 bpm) exercise, whereas at SL, the increase was only by 16 bpm (137±6 to 153±4 bpm) at 118 W, with no effect at maximal exercise (181±2 bpm). Despite restoration of maximal HR to SL values, glycopyrrolate had no influence on Q, which was reduced at ALT. Breathing FIO2=0.55 at peak exercise restored Q and power output to SL values. Conclusions: Enhanced parasympathetic neural activity accounts for the lowering of HR during exercise at ALT without influencing Q. The abrupt restoration of peak exercise Q in chronic hypoxia to maximal SL values when arterial PO2 and SO2 are similarly increased suggests hypoxia-mediated attenuation of Q.